การปรับตัวของแรงงานหญิงข้ามชาติชาวเมียนมาร์ในอำเภอเมือง จังหวัดเชียงใหม่ ภายใต้นโยบายความมั่นคงของชาติ - กิรวาที, เปรมวดี (Community and Social Development Journal, 2016)
A study of The Adaptation of Myanmar Women Trans border Labor in Muang, Chiang Mai district under Thai National Security Policy; its objective; 1) To study the methods of adaptation of Myanmar migrant women. 2) To study the factors which affect the adaptation of Myanmar migrant women. 3) To study the adaptation techniques of Myanmar migrant women under the Directives and policy guidelines of the state of Thailands measures to build national security. In this study, the researchers used an interview process, group discussions, and observations of participants. The target groups are Myanmar women, aged between 20-50 years. The study followed the transition from Myanmar migrant workers into Myanmar in Thailand. These women will have to adapt on many levels and in various contexts. The adjustments made are in the household, in the area of work, and adaptations to life under the Thai state security policy.